Teori Manajemen Pendidikan Islam - Nurul Faizatus Sholikah; Sunarto Sunarto (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
Educational management is an essential element in the management of educational institutions, including the effective and efficient arrangement of resources to achieve educational goals. This study examines Henry Fayol's management theory and its implementation in Islamic educational institutions. With a qualitative approach based on literature review, this study explores Fayol's five main management functions of planning, organizing, directing, coordinating, and controlling adapted according to Islamic values. The results of the study indicate that the application of Fayol's management principles can improve operational efficiency, strengthen the integration of Islamic values ​​in education, and create synergy between academic and spiritual aspects. Principles such as division of labor, authority and responsibility, discipline, unity of command, and unity of direction support the systematic and structured management of educational institutions. The adaptation of this theory in the context of Islamic education includes holistic strategic planning, organizing based on Islamic values, directing with moral leadership, coordination through deliberation, and control that focuses on achieving educational goals that include academic and spiritual aspects. This study concludes that the integration of Fayol's management theory with Islamic values ​​provides a comprehensive framework for managing Islamic educational institutions effectively and efficiently, while producing competent graduates with high moral integrity.